A case of spontaneous pneumomediastinum following exacerbation of bronchial asthma in adolescents - Jasmani, Asraf Haslam; Lee, Fei Yee; Ahmad Zaidi, Ahmad Al Hafeez; Khazalle, Muhammad Haekal; Mamat, Ahmad Zuhdi (Universiti Putra Malaysia Press, 2022)
Lack of knowledge in the management of spontaneous pneumomediastinum condition is attributable to its scarcity. Hypothetically, this condition arose during the exacerbation of bronchial asthma, leading to a recurrent forceful cough that increased the intraalveolar pressure and alveoli perforation. We present a 14-year-old boy with three days history of progressively worsening shortness of breath and chest pain radiating to the neck following exacerbation of bronchial asthma. Clinically, he was stable, despite remarkable subcutaneous emphysema over the anterior chest wall and the neck. Lung examination was unremarkable. There was substantial radiological evidence of subcutaneous emphysema, pneumomediastinum, pneumopericardium and pneumorrhachis. He was managed expectantly with oxygenation, control of bronchial asthma symptoms and analgesia. Subsequently, his symptoms resolved, and a complete resolution was seen as evident by radiological assessment. Spontaneous pneumomediastinum with pneumopericardium, pneumorrhachis and subcutaneous emphysema is a rare condition that requires prompt identification to prevent if from becoming a life-threatening condition.